2020
DOI: 10.1177/1941874420913715
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between Hyperchloremia and Acute Kidney Injury in Patients With Acute Ischemic Stroke

Abstract: Background and Purpose: While an association between hyperchloremia and worse outcomes, such as acute kidney injury and increased mortality, has been demonstrated in hemorrhagic stroke, it is unclear whether the same relationship exists after acute ischemic stroke. This study aims to determine the relationship between moderate hyperchloremia (serum chloride ≥115 mmol/L) and acute kidney injury in patients with ischemic stroke. Methods: This is a multicenter, retrospective, propensity-matched cohort study of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…19,20 Regarding the association between hyperchloremia and mortality, the study presents a similar RR to the investigations of Aguilar (RR=1.88; CI=1.41-2.51) 17 and Medina in a cohort with characteristics similar to the of the current work, in which they found (RR=3.12; CI=95%: 2.16-4.49). 16 Regarding the association with kidney failure, the results of this study agree with those of Haller, with a RR=1.91 (CI=95%: 1.01-3.59) 15 and Medina with a RR= 1.76 with a CI=95%: 1.42-2.17. 16 Based on these results, it can be stated that chloride disturbances are associated with a higher risk of negative outcomes in critical medicine.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…19,20 Regarding the association between hyperchloremia and mortality, the study presents a similar RR to the investigations of Aguilar (RR=1.88; CI=1.41-2.51) 17 and Medina in a cohort with characteristics similar to the of the current work, in which they found (RR=3.12; CI=95%: 2.16-4.49). 16 Regarding the association with kidney failure, the results of this study agree with those of Haller, with a RR=1.91 (CI=95%: 1.01-3.59) 15 and Medina with a RR= 1.76 with a CI=95%: 1.42-2.17. 16 Based on these results, it can be stated that chloride disturbances are associated with a higher risk of negative outcomes in critical medicine.…”
Section: Discussionsupporting
confidence: 84%
“…14 Haller et al describe an association between hyperchloremia and acute renal failure and number of hospital days, calculating a relative risk (RR) of 1.91 (95% CI: 1.01-3.59) for acute renal failure and hospital days (16 days vs 12 days, p=0.03); however, they failed to establish the association between hyperchloremia and mortality. 15 In Colombia, there is a single retrospective cohort study led by Medina et al, in which the relationship between hyperchloremia and mortality in critical patients was analyzed, finding a RR=3.12 (CI=95% 2.16-4.49) (p<0.001) for mortality and a RR =1.76 (CI=95% 1.42-2.17) (p<0.001) regarding the development of acute renal failure. 16…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 25, 2022. ; https://doi.org/10.1101/2022.07.24.22277969 doi: medRxiv preprint 3 months, MRS invariably had hyperchloremia, but an independent association could not be found. Some of the past studies found similar trends where hyperchloremia was associated with bad long term outcome in stroke (16) (17). Causes of hyperchloremia need to be looked further as any excessive use of intravenous infusions, presence of normal anion gap metabolic acidosis, or acute kidney injury and an attempt should be made to determine the causal relationship between hyperchloremia and poor outcome, if any (18).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 98%